GAGASAN EGALITARIANISME DALAM PERMAINAN DOLANAN SEBAGAI MEDIA PENDIDIKAN KARAKTER ANAK SEKOLAH DASAR - Tristaningrat, Made Adi Nugraha (PANGKAJA: JURNAL AGAMA HINDU, 2018)
This study aims: 1) to Integrating Dolanan in the local content of Egalitarinism is the internalization of the value of character education into learning so that the result is an awareness of the importance of values, and 2) to forming a positive character for children and habituation of personality values into the behavior of everyday learners through learning process both in and out of the classroom. In fact, in line with the condition of the technology and science content learned, this moral education has been abandoned by many schools. Traditional games can be an alternative that can be incorpo- rated into game activities to hone and develop matters relating to character education. The result of research that is 1) Dolanan with egalitarian conceptcan be integrated into the local content SD Ed- ucation is the internalization of the value of character education into the learning so that the results obtained awareness of the importance of values, and 2) Dolanan with egalitarian conceptcan can form a positive character for children and the habituation of personality values into the behavior of everyday learners through learning process both in and out of the classroom.